Pertumbuhan dan Hasil Kacang Hijau (Vigna radiata L.) dalam Tumpangsari dengan Jagung (Zea mays L.) pada Penanaman Ketiga Di Tanah Entisol Semi Arid yang Mengandung Residu Kompos Biochar dan Pernah Ditanami Jagung Secara Monokultur - Bonifasius Nahak (Savana Cendana, 2021)
This study aims to determine the types of residues of several types of biochar compost that can increase the growth and yield of green bean plants intercropped with maize in semi arid entisol soil. To determine the dosage of biochar compost which can increase the growth and yield of green bean plants which are intercropped with maize in semi arid entisol soil. This research was conducted in August - October 2020 on the land of the Faculty of Agriculture, University of Timor, Sasi Village, Kefamenanu City District, North Central Timor Regency, East Nusa Tenggara Province. This study used a 3 × 3 stripe plot design that was repeated 3 times. The first factor is the type of siever in the biochar compost which consists of three treatments, namely pure biochar (P0), chicken manure, and cow dung while in the second factor the biochar compost is: 0 t / Ha, 5 t / Ha and 10 t / Ha. Thus the treatment combination there are 9 units, each of which is repeated 3 times so that there are 27 treatment units. The results showed there was an interaction between the residual treatment of biochar compost and the dose of biochar compost at soil temperature parameters 28 DAS and plant height 42 DAS. Treatment of chicken manure biochar compost residue is the best treatment in increasing the growth and yield of mung bean plants. This was evidenced by the highest values for the parameters of plant height, number of leaves, fresh weight of stover, number of root nodules, number of effective root nodules, number of ineffective root nodules, stubborn dry weight, number of pods per plant, weight of seeds per plot, and weight of seeds per plant. Ha. Treatment of 10 t / ha biochar compost is the best treatment in increasing the growth and yield of mung bean plants. This was evidenced by the highest values for the parameters of fresh weight of stover, number of effective nodules, dry weight of stunts, pod length, number of pods per plant, weight of seeds per plant, weight of 100 seeds, weight of seeds per plot, and weight of seeds per Ha.